Evolution of the Health Care System in the USA – Obama and Trump Reforms - Joanna NIZNIK (Communications of International Proceedings, 2020)
The evolution of the American health care system observed in recent years, caused by the reform of Barack Obama and the activities related to taking up office by Donald Trump, raises questions about the impact of the introduced changes on the health care system. In order to address the research problem, the article presents the most important stages of the development of the health care concept from the USA, the construction of the system, the evolution of the system in the years 2014-2016 and indicates the key adjustments to the system brought about by the decisions of the current president. Research methods based on inductive reasoning connected with studies of the subject literature, search of the Internet resources and available databases were employed. On the basis of information included in the aforementioned sources in the theoretical part, the analysis of a theoretical and compilation character was carried out. Within the empirical part, a secondary research was carried out, including in-depth analysis of the organisation and financing of the health care in the USA, the collected material was synthesised and the most important changes taking place in the health system were pointed out. The current shape of the health system was strongly influenced by the reform called Obamacare, which imposed on residents under threat of penalties the obligation of insurance, while at the same time introducing a whole catalogue of incentives in the form of reliefs and tax exemptions. Public funding was extended by lowering income criteria of persons covered by such assistance. The support was provided for the creation of new institutions - health platforms - to facilitate the comparison of insurance offers and the purchase of insurance. For the first time, 10 types of benefits were indicated, which must be part of every health plan (including prophylactic measures) and the only criterion differentiating the amount of health care contributions was age. At the same time, insurance companies were required to conclude insurance contracts. The American health system will evolve in the direction determined by the health policies of successive presidents and parliaments. The current measures are designed to reduce the financial burden on businesses, the insured people and insurance companies, as well as on federal and state budgets, by waiving penalties for non-insurability and by eliminating subsidies provided to insurance companies for low-income individuals, which may in the future slow down the trend of increasing numbers of people having access to medical services.
Keywords: Health Care System; Obama Reform; America Health Care System.